The association between facebook usage and student engagement at Universiti Teknikal Malaysia Melaka (UTeM) City Campus / Ungku Norazekin Ungku Mohd Noor - Ungku Mohd Noor, Ungku Norazekin (Faculty of Business and Management, 2016)
This study was conducted to explain the association between Facebook usage and student engagement. Facebook divided into three, facebook use, facebook activities and facebook time spent. The subject area for this study is University Teknikal Malaysia Melaka (UTeM) City Campus. This study involves 262 respondents of students in utem City Campus. A pilot survey study was carried out to identify the problem of using questionnaire with 30 respondents from students in utem City Campus. The 274 structural questionnaire then has been used to collect data from the respondents and the answer received only 262 respondents complete answer the questions were analyzed.